Most reports received by MYCC are about bid-rigging - Borneo Post, (KK) (Borneo Post (KK), 2017)
KUALA LUMPUR: The Malaysian Competition Commission (MyCC) received 340 complaints on various cases under the Competition Act since 2012 until October 2017, involving the imposition of penalties amounting to RM23.4 million.